Pengembangan Media Pembelajaran Interaktif Teknik Digital menggunakan Software Adobe Flash - Pujiana Pujiana; Taali Taali (Jurnal Pendidikan Teknik Elektro, 2020)
This research is motivated by the lack of active role of students in the learning process due to the limited learning media used in learning. Lecturers are more likely to use printed learning resources that are not able to present the material required for simulation so that it is difficult for students to understand and is not interactive yet. Therefore, it is necessary to develop interactive learning media using Adobe Flash CS6 software which is designed to help students in more active learning. This study aims to produce interactive learning media using adobe flash CS6 software that is valid and practical. This study uses a Research and Development (R&D) method with a 4D development model which is divided into the stages of defining, designing, developing, and disseminating. The subjects of this study were students of semester 3 class 2TEIA Diploma-4 Electrical Engineering, Padang State University, 2020/2021 academic year. Based on the research results, testing the validity of interactive learning media obtained an average value of 0.81% with the valid category. The results of the practicality test for lecturers were obtained by 92.6% in the very practical category and the results of the practicality test by students were obtained by 83.4% with the practical category. It can be concluded that the resulting interactive learning media using Adobe Flash CS6 software is valid and practical for use in the teaching and learning process in Digital Engineering subjects.